2020
DOI: 10.1136/bmjopen-2020-038091
|View full text |Cite
|
Sign up to set email alerts
|

Readability in printed education materials for Chinese patients with systemic lupus erythematosus: a mixed-method design

Abstract: ObjectivesTo assess the readability of printed education materials (PEMs) for patients with systemic lupus erythematosus (SLE) and to explore the perceptions of patients with SLE with different health literacy regarding the readability of PEMs.DesignA mixed-methods study, including a cross-sectional survey and semistructured interviews.SettingThe SLE PEMs were collected from 13 hospitals in China. The interviews were conducted in the Department of Rheumatology of a hospital in Hefei, China.ParticipantsIn the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As a result, it is critical that health-related material on websites be appropriate for the reader and thoroughly assessed before being used. There have been numerous studies published in the literature on the readability, reliability, and quality of online information in various disorders (10)(11)(12)(13).…”
Section: Original Papermentioning
confidence: 99%
“…As a result, it is critical that health-related material on websites be appropriate for the reader and thoroughly assessed before being used. There have been numerous studies published in the literature on the readability, reliability, and quality of online information in various disorders (10)(11)(12)(13).…”
Section: Original Papermentioning
confidence: 99%
“…Over time, the patients in the observation group perceived differences between their own disease information and needs during the original intervention and follow-up, and the information and understanding methods they could obtain from the manual changed. [ 4 ] According to the expression of information acquisition and the results of this item in the third month of follow-up in the observation group, the patients in the observation group were interested in their own diseases and rehabilitation content in the short-term intervention. The KAP model combined with MI health education can help patients enhance their motivation for change and self-efficacy and effectively adjust their lifestyle with the knowledge they have mastered.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] A survey on medication adherence in 144 patients with SLE has revealed that although 43.1% of patients were compliant, their long-term compliance reduces over time after the disease becomes stable. [4] Although female patients had better pathogenesis and outcomes than male patients, they have worse negative emotional events such as disease cognition, anxiety, depression, and fatigue, and are more vulnerable to SLE affecting health behavior. [5][6][7][8] Lower health literacy was associated with worse patient-reported outcomes and higher disease activity in patients with SLE, especially in women.…”
Section: Introductionmentioning
confidence: 99%
“…However, interventional RCTs in mainland China focus on pharmacologic and biologic treatments, while the absence of interventions involving self-management, diet, education, exercise, and care reflects ignorance of the importance of comprehensive management for SLE patients among physicians in mainland China. Even in clinical practice, the importance of education and self-management of patients has been largely underestimated in mainland China ( 23 25 ), and it is necessary for researchers to explore localized nonpharmaceutical interventions in terms of nursing, education, and patient self-management. Based on that, coordinated efforts of physicians to establish a comprehensive and efficient clinical patient management system would support medication adherence, save medical resources, and help patients control their diseases.…”
Section: Discussionmentioning
confidence: 99%